A numerical simulation of tropical storm Chedza over south-eastern Africa - Rapolaki, Ramontsheng Sakia (Department of Oceanography, 2017)
Widespread flooding over parts of Malawi, Mozambique, and Madagascar occurred in January 2015. An impact assessment by the World Bank indicated huge damage to property, infrastructure, and agriculture over several regions in south-eastern Africa. The flooding was associated with tropical storm Chedza that developed in the Mozambique Channel on 11 January 2015. This study investigates the atmospheric circulation and potential mechanisms responsible for the heavy rainfall event that occurred between 11 and 17 January over Mozambique and Malawi using the Weather Research and Forecasting (WRF) model, the Global Forecast System (GFS) atmospheric reanalysis, satellite derived rainfall and wind data, and station rainfall data. Tropical Rainfall Measuring Mission (TRMM) rainfall estimates and rainfall station data indicated that southern Malawi and northern Mozambique experienced the majority of rainfall during the early stages of tropical storm Chedza while Madagascar experienced heavy falls when tropical storm Chedza tracked over the island on January 17. Furthermore, analysis of the station data revealed that the heavy rainfall over Mozambique occurred between 11 and 13 January with some stations recording about 80 % of their total January 2015 rainfall as resulting from this event. The WRF model run of the event indicated a low level easterly to southeasterly onshore flow over southern Mozambique that interacted with a northwesterly monsoonal flow to westerly flow along the northern flanks (periphery) of the storm in the northern Mozambique Channel, leading to surface moisture flux convergence in the regions of heavy rainfall. Furthermore, moisture from the southwest Indian Ocean was advected into the region during the heavy rainfall. It is suggested that multiple favourable factors which included strong moisture fluxes from the southwest Indian Ocean and equatorial South Indian Ocean, near surface convergence over the areas of heavy rainfall, and strong uplift acted together to create favourable conditions for the development of tropical storm Chedza and the associated heavy rainfall.